Farmer perspectives on introducing perennial cereal in Swedish farming systems: a sustainability analysis of plant traits, farm management, and ecological implications. Issue 5 (27th May 2016) - Marquardt, K.; Vico, G.; Glynn, C.; Weih, M.; Eksvärd, K.; Dalin, P.; Björkman, C.
Abstract: Agriculture is currently dominated by annual crops. A shift from annual to perennial cereals has been suggested as a way to improve the sustainability of agriculture. Such a shift may have impacts at multiple levels, from the field, to the farm, and the landscape. With a focus on Swedish farm production systems, farmers' views on the potential risks and possibilities of cultivating perennial cereals are discussed in light of the available knowledge regarding plant traits and ecological implications of perennial systems. Farmer interviews showed that potential changes in agricultural sustainability, if perennial cereals were to be introduced, are highly complex, and context specific. Perennial cereals could be part of a transition toward a more sustainable agriculture depending on how they are used in the local farming system and in the larger landscape. Efforts to increase the use of perennial crops require linking specific plant traits of the perennial crop to the properties of the farming systems where these crops would be employed.